2022
DOI: 10.1021/acs.analchem.2c04294
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Nucleic Acid Probe Based on 2′-Fluorinated DNA Functionalization for High-Fidelity Intracellular Sensing

Abstract: Traditional spherical nucleic acids (SNAs) based on gold nanoparticles (AuNPs) assembled through Au−S covalent bonds are widely used in DNA-programmable assembly, biosensing, imaging, and therapeutics. However, biological thiols and other chemical substances can break the Au−S bonds and cause response distortion during the application process, specifically in cell environments. Herein, we report a new type of SNAs based on 2′-fluorinated DNA-functionalized AuNPs with excellent colloidal stability under high sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…These results suggested that the interactions between CpG and Obsl1 were weaker and insufficient to form stable nanostructures; thus, the fluorine substitution in CpG might play a key role in constructing stable 2′F-CpG/Obsl1 NPs for vaccine applications. Fluorine atoms exhibit the highest electronegativity and can influence the physicochemical and electronic properties of other molecules via dispersion forces and dipole effects. Therefore, MD simulations were performed to study the interactions between 2′F-CpG and Obsl1. The molecular docking model of 2′F-CpG and Obsl1 indicated that the introduction of a fluorine atom into CpG enhanced the adsorption capacity of 2′F-CpG to amino acid residues (Figure c,d and Video S1), which was confirmed by MD (Figure e,f).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the interactions between CpG and Obsl1 were weaker and insufficient to form stable nanostructures; thus, the fluorine substitution in CpG might play a key role in constructing stable 2′F-CpG/Obsl1 NPs for vaccine applications. Fluorine atoms exhibit the highest electronegativity and can influence the physicochemical and electronic properties of other molecules via dispersion forces and dipole effects. Therefore, MD simulations were performed to study the interactions between 2′F-CpG and Obsl1. The molecular docking model of 2′F-CpG and Obsl1 indicated that the introduction of a fluorine atom into CpG enhanced the adsorption capacity of 2′F-CpG to amino acid residues (Figure c,d and Video S1), which was confirmed by MD (Figure e,f).…”
Section: Resultsmentioning
confidence: 99%
“…Spherical nucleic acids enzymes (SNAzymes) are usually fabricated using functional DNA strands decorated on gold nanoparticles (AuNPs), which are extensively applied in biosensing depending on their ease of synthesis, programmable functionalization, and high stability [1][2][3][4][5]. Compared to other DNA sequences, G-quadruplex (G4) exhibits higher density of the nucleic acid layer after it is modified on the surface of AuNPs through the Au-S covalent band [6], showing good peroxidase-mimicking activity with the presence of the cofactor hemin [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%